Giant omental inflammatory myofibroblastic tumour causing intestinal obstruction: a rare care report and review of literature - Kumar, Utkarsh; Thami, Gaurav; Kamra, Hemlata; Agarwal, Nivesh (International Surgery Journal, 2020)
It is a rare mesenchymal tumour of intermediate biologic potential (according to World Health Organization), with unknown aetiology. It is benign tumour with malignant potential. It frequently recurs and rarely metastasizes. Abdominopelvic inflammatory myofibroblastic tumours have the recurrence rate of 85% so meticulous follow up is necessary. Complete surgical excision is the main stay treatment.